User interface design for the Asia elderly: a systematic literature review / Zehang Cheng and Kamal Sabran - Cheng, Zehang; Sabran, Kamal (2021)
According to statistics from the United Nations Department of Economic and Social Affairs, Asian communities are ageing faster and faster, enabling the elderly to use new technology user interfaces to solve their problems, easing the pressure on the elderly social security system. Although new media technology helps people's lives become more convenient, it is difficult for the elderly to learn and use. This article mainly reviews relevant literature on interface design for the elderly in Asia. The goal is to discover current methods and trends in designing interfaces for Asian seniors. The review found that relevant research mainly helps the elderly strengthen their ability to live alone, improve their physical health, and provide social information for the elderly. The method is mostly user-centric interface design. We hope to lay a foundation for continuing research on this topic and suggest the current lack of research and future developmen